Development of Learning Media to Enhance Students' Digital Literacy: A Bibliometric Analysis - Purwanto, Andik; Hamzah, Syukri; Wardana, Rendy Wikrama; Yanti, Fitri April; Butali, Reygan A. (UIN Fatmawati Sukarno Bengkulu, 2026)
This research aims to determine the need for the development and application of learning media as an effort to improve students' digital literacy. The research method carried out is the determination of keywords, namely